Evaluation of School Absenteeism and Affecting Factors in Child Patients with Epilepsy - Ayşegül Danış; Halil Celik (Genel Tıp Dergisi)
Introduction Epilepsy is one of the common chronic diseases in childhood and puberty with a prevalence of nearly 0,5%. The children with epilepsy may suffer from such problems as school absenteeism and drop-out. This study is, therefore, intended to determine the frequency of school absenteeism in the children with epilepsy and the factors affecting it. Material-Method The children ranging from 12 to 17 years of age, diagnosed with epilepsy for at least one year in the department of pediatric neurology at Konya City Hospital and Bolu Abant İzzet Baysal University, were included in the study. The patients who were enrolled at a school in 2012-22 training and education year in the absence of a mental or motor comorbidity that would be a hindrance to their attendance to school were included in the study. As the control group, the volunteers of the same age who applied to the department of pediatric health and diseases of our hospital for routine control in the absence of any health problem were included in the same study. Results 59 children diagnosed with epilepsy, ranging from 12 to 17 years of age, were admitted to the study and 51 children of the same age and sex group with no chronic diseases who applied to pediatric polyclinics were admitted to the study. 34 (56.7%) of the patients with epilepsy and 23 (45.1%) of the control group were males. All of the patients were absent from the school for more than one day and 4 (6,8%) patients had dropped out of the school due to their long absenteeism. None of the children in the control group dropped out of the school. The median number of the days of patients’ absenteeism was 4, while that of the control group was 1. The number of the days of patients’ absenteeism was higher than that of the control group, and it was statistically significant (p